World Health Organization Regime Effectiveness in Controlling COVID-19: Case Study of Malaysia, Thailand, and Indonesia - Ilkodar, Saptopo Bambang (Jurnal Paradigma, 2023)
The World Health Organization (WHO) is the only international organization to be given authority by the Charter of the United Nations to promote and protect the health of all people. Then it is not surprising that people look after the response and action of the WHO when COVID-19 cases explode worldwide.  Observing the response of the WHO, some analysts criticized the organization for late, incomprehensive, and unsystematic policy. Some even blame the way the organization work, that is reactive rather than predictive, the shortage of the budget, and the decision-making process that is not transparent.            This paper intends to analyze the effectiveness of the WHO's rule, norms and regulation in controlling the spread of the COVID-19. It tries to answer the question of how effective the WHO regime is in controlling COVID-19 spread. Using the theory of regime effectiveness, it studies the case of Malaysia, Thailand, and Indonesia. The three countries are chosen because WHO has appreciated Malaysia and Thailand for their compliance with International Health Regulations (2005) (IHR) core capacity requirements and have strong capacity and self-sufficiency in outbreak preparedness and response. Meanwhile, Indonesia faced considerable difficulties at the beginning of the pandemic, but currently Indonesia achieves better performance in controlling the pandemic than that Malaysia and Thailand. Keywords: World Health Organization, International Health Regulation, COVID-19, international regime, effectiveness